2015
DOI: 10.1111/codi.12885
|View full text |Cite
|
Sign up to set email alerts
|

How do patients score cosmesis after laparoscopic natural orifice specimen extraction colectomy?

Abstract: Depending on the scoring system used, the cosmetic outcome may be better after NOSE colectomy than conventional laparoscopy in patients having surgery for endometriosis. The comprehensive body image questionnaire, being shorter and easier to use, could be a valid tool for assessing cosmesis after NOSE procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 25 publications
0
17
0
1
Order By: Relevance
“…Wolthuis et al [31] described in detail how patients score for cosmetic results after laparoscopic NOSE colectomy. In our meta-analysis, three studies [22,24,27] reported the cosmetic result after surgery using a scale ranging from 1 (poor) to 10 (excellent).…”
Section: Cosmetic Resultsmentioning
confidence: 99%
“…Wolthuis et al [31] described in detail how patients score for cosmetic results after laparoscopic NOSE colectomy. In our meta-analysis, three studies [22,24,27] reported the cosmetic result after surgery using a scale ranging from 1 (poor) to 10 (excellent).…”
Section: Cosmetic Resultsmentioning
confidence: 99%
“…Superior outcomes in terms of postoperative pain control, time to first bowel function, hospital length of stay, reduced incisional complications, and improved cosmesis have been demonstrated. 17 , 19 22 It should be noted that studies demonstrating these superior outcomes had strict inclusion criteria. Careful examination of patient characteristics in these studies can be used to extrapolate themes that can aid in selecting patients who can most benefit from NOSE in colorectal surgery.…”
Section: Potential Benefitsmentioning
confidence: 99%
“…Improved cosmesis has been assumed to be superior in patients undergoing NOSE compared to conventional specimen extraction; however, Wolthuis et al 22 investigated this more objectively in a case-matched series. They found that cosmesis was significantly better in the NOSE group as evaluated by a body image questionnaire and the Patient Scar Assessment Questionnaire.…”
Section: Potential Benefitsmentioning
confidence: 99%
“…[3][4][5] NOSES surgery has several distinct advantages as a result of its dedication for extremely minimal invasiveness based on a strict principle of contamination-free surgical manipulations. 2,6,7 Compared with laparoscopy-assisted surgery, patients receiving NOSES tend to experience an increased rate of comfortability 8 and a comparable frequency of complications with a shortened time for recovery and hospital stay. 7,9−11 However, improper application of NOSES for patients with upper RC may led to complications such as bacterial contamination and anastomotic bleeding and leak.…”
Section: Introductionmentioning
confidence: 99%